(3QSGdI aj GdbVGA hGdbOQs - (3GdUbQj, GdeWjQaj, GdGMSGFj, GdHMQGfj, YeGO GdOjf, CMeO Hf Rjf GdOjf Hf EHQGgje Hf UbQ, J (B1241(3g`s ((3eMeO bdj Hf ejQRG GdNhFjfjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3hHYO, ajbhd GdYHO GdeScjf CMeO Hf Rjf GdOjf GdCMSGFj gPg cdeGJ PGJ JHjjf hHjGf aj GdbOQ(B...s
(3BNQgG (B:s
(3ef jVHW MOhO gPG GdcdGe abO NUe ef NGdag hCeKGd Pdc cKjQ hHjGf gPg GdCNHGQ jYQa eeG eVi hGdMeO ddg QH GdYGdejf(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B129s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B185s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B185s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJhMjO hGdedd hGdfMds